More than a rock : essays on art, creativity, photography, nature, and life - Tal, Guy (Rocky Nook, 2015)
Ostensibly about landscape photography, More Than a Rock is a passionate and personal book about creativity and expression. In this series of essays, photographer and teacher Guy Tal shares his thoughts and experiences as an artist who seeks to express more in his images than the mere appearance of the subject portrayed. Tal makes an argument to consider creative landscape photography-expressing something of the photographer's conception through the use of natural aesthetics-as a form of visual art that is distinct from the mere representation of beautiful natural scenes. Tal covers topics such.